Developing a New Appliance to Dissipate Mechanical Load on Teeth and Improve Limitation of Vertical Mouth Opening - Takashi Satomi; Toshiaki Tanaka; Takehito Kobayashi; Mituyoshi Iino (Stilus Optimus, 2013)
Objectives: The principle of leverage to superpose the convex surfaces of two shells was applied to develop a device for treating limitation of mouth opening and called it the "shell-shaped mouth opener" and analyzed pressure on the teeth with the TheraBite® appliance and the shell-shaped mouth opening appliance. Material and Methods: To compare the TheraBite® appliance and the shell-shaped mouth opening appliance, pressure on the teeth in the dentition model with both devices was analyzed using the Inastomer® flexible conductive sensor. Results: The load was better dispersed to each tooth in the shell-shaped mouth opening appliance in the all quadrants compared to the TheraBite® appliance. Conclusions: The present study revealed that the shell-shaped mouth opening appliance which was originally invented in our lab, dissipated the mechanical load on teeth more evenly than the TheraBite® appliance.